2020
DOI: 10.1007/s11111-020-00354-6
|View full text |Cite
|
Sign up to set email alerts
|

Deepwater Horizon oil spill exposure and child health: a longitudinal analysis

Abstract: The BP Deepwater Horizon oil spill (DHOS) created widespread concern about threats to health among residents of the Louisiana Gulf Coast. This study uses data from the Resilient Children, Youth, and Communities study-a longitudinal cohort survey of households with children in DHOS-affected areas of South Louisiana-to consider the effect of DHOS exposure on health trajectories of children, an especially vulnerable population subgroup. Results from latent linear growth curve models show that family DHOS exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Oil and associated chemical components have a wide range of known or putative toxic outcomes, including endocrine disrupting, carcinogenic, cytotoxic, immunotoxic, mutagenic, and genotoxic effects (Solomon and Janssen, 2010;Bhattacharya et al, 2016;Du et al, 2016;Laffon et al, 2016;Doctors for Environment Australia, 2019;Holme et al, 2019). Exposures can occur through physical contact with contaminants in air, water, or on materials; disruptions of routine behaviors; socioeconomic impacts; or other pathways (Hobfoll, 1991;Eisenberg and McKone, 1998;Slack et al, 2020).…”
Section: Health Effects On Non-workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil and associated chemical components have a wide range of known or putative toxic outcomes, including endocrine disrupting, carcinogenic, cytotoxic, immunotoxic, mutagenic, and genotoxic effects (Solomon and Janssen, 2010;Bhattacharya et al, 2016;Du et al, 2016;Laffon et al, 2016;Doctors for Environment Australia, 2019;Holme et al, 2019). Exposures can occur through physical contact with contaminants in air, water, or on materials; disruptions of routine behaviors; socioeconomic impacts; or other pathways (Hobfoll, 1991;Eisenberg and McKone, 1998;Slack et al, 2020).…”
Section: Health Effects On Non-workersmentioning
confidence: 99%
“…How people adapt to repeated exposure to stress depends on an array of psychological, socio-demographic, economic, social, physical, and other variables (McEwen, 2005;Norris et al, 2008). Inhabitants of the Gulf region are particularly susceptible to oil spill health impacts due to widespread, preexisting health disparities, continuing exposure to contaminants, and location in a disaster-prone region (Lichtveld et al, 2016;Slack et al, 2020). Not surprisingly, the DWH oil spill, like Hurricane Katrina and other disasters, "had its greatest impact among those with the least" (Abramson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Are Linked Disasters occurring in the Gulf impact not only the biota and ecosystems of this large marine ecosystem but also the people that inhabit its shores. This is especially true because the Gulf is situated in a naturally precarious region that is subject to a variety of natural and human-made threats, and the area population exhibits health disparities and suffers continued exposure to environmental contaminants (Lichtveld et al, 2016;Slack et al, 2020). The DWH disaster had extensive adverse physical and mental human health impacts for some responders, cleanup crews, and residents in coastal communities.…”
Section: Gulf Health and Human Healthmentioning
confidence: 99%
“…However, adverse psychological effects were common among those exposed to the spill physically or through associated socioeconomic impacts (e.g., job/income loss; Finucane et al, 2020). Natural resourcedependent communities (e.g., fishers) were particularly vulnerable to mental health effects (Cope et al, 2013;Parks et al, 2020;Slack et al, 2020), as were those who suffered socioeconomic disparities. While children are of special concern for negative health effects from spill exposure and exhibited some impacts (Abramson et al, 2010;Slack et al 2020), studies of children's seafood consumption (Sathiakumar et al, 2017) and beach play (Ferguson et al, 2020) showed little if any additional health risks associated with potentially contaminated seafood or exposure to contaminated beach sediments (Sandifer et al, 2021, in this issue).…”
Section: Gulf Health and Human Healthmentioning
confidence: 99%
“…16 A longitudinal extension of this study in southern Louisiana by Slack, et al found that familial physical and economic oil spill exposure negatively influenced initial child health, and the effects of job or income loss persisted. 17 Studies of Louisiana and Mississippi adolescents found significant associations between oil spill-related stress and post-traumatic stress disorder and poor self-reported competence and well-being. 18,19 However, there remains a gap in the literature on DHOS's impact on children throughout the entire Gulf Coast, including Alabama and Florida, as well as how children's post-DHOS health outcomes were shaped by race/ethnicity and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%